Incidence and Predictors of Pregnancy among Women on ART in Debre Markos Referral Hospital, Northwest Ethiopia: A Five-Year Retrospective Cohort Study - Maru Meseret; Alemayehu Shimeka; Alemayehu Bekele (AIDS Research and Treatment)
Globally, death of women due to HIV/AIDS related causes during pregnancy or within 42 days after pregnancy was estimated to be 37,000. In Ethiopia, 42,900 pregnant women living with HIV gave birth in the year 2011. This study was aimed to assess incidence and predictors of pregnancy among women on ART in Debre Markos Referral Hospital, Northwest Ethiopia. A retrospective cohort study was conducted using data recorded from September 2011 to August 2015. Data was extracted from February to March, 2016, from 1,239 records and analyzed using SPSS version 16. A Kaplan-Meier survival analysis was used to estimate the probabilities of being pregnant. The Cox proportional hazards model was done and results were expressed using hazard ratios with 95% CI. A total of 1,239 women on ART were included in the study. The incidence of pregnancy was 49.2 per 1,000 person-years. Living in rural, being married, being widowed, being unemployed, and having <2 children at enrollment were found to be positively associated with being pregnant. The incidence of pregnancy among women on ART was found to be considerable. Provision of family planning and other reproductive health interventions have to be coupled with the ART service to address the problem.